Effects of Mineral Elements and Annealing on the Physicochemical Properties of Native Potato Starch - Thomann, Johanna A.; Polhuis, Michael; Lasorsa, Alessia; Heeres, Hero J.; Heeres, André (ChemEngineering, 2024)
Native potato starch is an excellent carrier of minerals due to its inherent ion exchange capacity. Mineral enrichment not only changes the nutritional value but also influences starch pasting and swelling properties. Hydrothermal treatments like annealing constitute a straightforward and green way to tune functional properties. Here, novel combinations of mineral enrichment and annealing were studied. Ion exchange was readily achieved by suspending starch in a salt solution at room temperature over 3 h and confirmed by ICP-OES. Annealing at 50 °C for 24 h using demineralized water or salt solutions strongly affected pasting, thermal, and swelling properties. The obtained XRD and DSC results support a more ordered structure with relative crystallinity increasing from initially 41.7% to 44.4% and gelatinization onset temperature increasing from 60.39 to 65.94 J/g. Solid-state NMR spectroscopy revealed no detectable changes after annealing. Total digestible starch content decreased after annealing from 8.89 to 7.86 g/100 g. During both ion exchange at room temperature and annealing, monovalent cations promoted swelling and peak viscosity, and divalent cations suppressed peak viscosity through ionic crosslinking. The presented combination allows fine-tuning of pasting behavior, potentially enabling requirements of respective food applications to be met while offering an alternative to chemically modified starches.